2004
DOI: 10.1111/j.1365-2869.2004.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

The nature of arousal in sleep

Abstract: SUMMAR Y The role of arousals in sleep is gaining interest among both basic researchers and clinicians. In the last 20 years increasing evidence shows that arousals are deeply involved in the pathophysiology of sleep disorders. The nature of arousals in sleep is still a matter of debate. According to the conceptual framework of the American Sleep Disorders Association criteria, arousals are a marker of sleep disruption representing a detrimental and harmful feature for sleep. In contrast, our view indicates ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
384
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 448 publications
(424 citation statements)
references
References 169 publications
19
384
0
2
Order By: Relevance
“…Alternatively, if we cannot reliably detect the presence of arousals during sleep but instead consider positive classifications on arousal epochs as correct, the precision of the classifier increases by a maximum of 31.3%. These findings are in line with earlier observations that body movements may follow cortical arousals during sleep [9]. However, the physiological consequences of these events are not limited to body movements.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Alternatively, if we cannot reliably detect the presence of arousals during sleep but instead consider positive classifications on arousal epochs as correct, the precision of the classifier increases by a maximum of 31.3%. These findings are in line with earlier observations that body movements may follow cortical arousals during sleep [9]. However, the physiological consequences of these events are not limited to body movements.…”
Section: Discussionsupporting
confidence: 83%
“…However, the physiological consequences of these events are not limited to body movements. In fact, the sympathetic surge corresponding to the occurrence of an arousal is also manifested at cardiac level [9]. Interestingly, recent work in sleep/wake classification showed that the addition of cardiac features to actigraphy increases sensitivity to the wake class [7], [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…K-COMPLEXES AND SLEEP SPINDLES-Irregular, relatively sharp potentials occur sporadically in the scalp EEG during non-REM sleep (Loomis et al, 1938;Roth et al, 1956) and under anesthesia (Amzica and Steriade, 1997;Steriade and Amzica, 1998b). This pattern, termed K-complex (Loomis et al, 1938), can arise either spontaneously or be evoked by stimuli of all modalities, including slight positional changes in bed (Halasz et al, 1985;Halasz et al, 2004). Again, in light of the mechanisms of slow oscillations the origin of the K-complex can be redefined.…”
Section: Slow (<1 Hz) Rhythms-mirceamentioning
confidence: 99%
“…Because sensory stimuli can trigger UP states (Petersen et al, 2003), this might explain why at least some K complexes are associated with sensory inputs in sleeping subjects (Halasz et al, 2004).…”
Section: Slow (<1 Hz) Rhythms-mirceamentioning
confidence: 99%